An Assessment of the Validity and Reliability of the Pediatric Child Health Utility 9D in Children with Inflammatory Bowel Disease - Naazish S. Bashir; Thomas D. Walters; Anne M. Griffiths; Wendy J. Ungar (Children, 2021)
Health utilities relevant to children are lacking, compromising health funding and policy decisions for children. The Child Health Utility 9D (CHU9D) is a recently developed preference-based health utility instrument designed for use in children. The objective was to examine the validity of the CHU9D in a cohort of 285 Canadian children aged 6.5 to 18 years of age with Crohn’s disease (CD) and ulcerative colitis (UC), (collectively inflammatory bowel disease (IBD)). The correlation and agreement between paired CHU9D and Health Utility Index (HUI) assessments were determined with Spearman coefficients and Bland–Altman levels of agreement. Total and domain utilities were calculated for the CHU9D using Australian adult and youth tariffs. Algorithms for HUI2 and HUI3 were used. Domain correlations were determined between domains with expected overlap between instruments. In CD and in UC, correlations between CHU9D, HUI2, and HUI3 utilities ranged between 0.62 to 0.67 and 0.67 to 0.69, respectively (p < 0.05). CHU9D utilities were lower using youth tariffs compared to adult tariffs. A large range in health utilities suggested a heterogeneous quality of life. The CHU9D is a good option for preference-based utility measurement in pediatric IBD. Additional research is required to derive pediatric tariffs to conduct economic evaluation in children.